Science, Technology, Society, Environment Training Model to Improve Positive Attitudes of Early Childhood Teachers in the Environment - Habibi, MA Muazar (Jurnal Pendidikan Indonesia, 2023)
The lack of positive attitude may be caused by the weak implementation of environment education. One of the ways to solve the problem is by preparing prospective early childhood teachers to have the ability to instill environment concern to their students as early as possible so that the students grow up becoming people who care about the environment. The purpose of this research is to develop training scenarios on environmental education using Science, Technology, Society, Environment (STSE) model integrated into scientific thematic lessons, particularly for prospective early childhood teachers. This research is kind of development research. There were three aspects assessed by these experts namely usability, accuracy, and feasibility employing quantitative and qualitative data analyses. User judgment came from the prospective teachers done through interviews, and the data from these interviews were analyzed quantitatively and qualitatively. The results involved three expert assessments in the field of early childhood, environmental education, and educational technology, although further analysis is required. Subsequent investigation conducted on the subject user group, indicating a positive value of 83.3%, in support of the product. Therefore, the efficiency test results showed the training on environmental education using the Environmental Education Training with STSE model and integrated with scientific thematic lessons, were known to enhance 32.44% of all aspects of the prospective teacher's positive attitudes on the environment.